The Impact of the Index Card Match Model on Mathematics Learning Motivation in Early Adolescence - Indrawati, Nenny; Nurhidayah, Nurhidayah; Sumanik, Novike Bela; Ismail, Ismail (PPSDP International Journal of Education, 2025)
The objective of this research was to examine whether the Index Card Match learning model influences the mathematics learning motivation of seventh-grade students at SMPN 4 Majene. Two hypotheses were formulated for this study: (1) the application of the Index Card Match learning model has a significant impact on students’ motivation to learn mathematics (H1), and (2) the application of the Index Card Match learning model has no significant impact on students’ motivation to learn mathematics (H0). A quasi-experimental design with a pre-test–post-test control group approach was utilized to conduct the study. The hypothesis was tested through N-Gain analysis, revealing that the mean N-Gain score of the experimental group exceeded that of the control group. This finding suggests that the Index Card Match learning model resulted in a significantly greater improvement than the conventional direct instruction method. Statistical testing at the 0.05 significance level produced a sig value of 0.000 < 0.05, leading to the rejection of H0 and acceptance of H1. Therefore, it can be concluded that the Index Card Match model has a significant positive influence on the mathematics learning motivation of seventh-grade students at SMP Negeri 4 Majene.